Relationship Between Family Social Support with Anxiety of Postpartum - Bila, Zakia Jihan Salsa; Santoso, Budi; Akbar, Muhammad Ilham Aldika (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Anxiety is a psychological disorder that often occurs during the puerperium. The prevalence of anxiety disorders in the world's population is generally 3-8% with most cases in the productive age. Postpartum anxiety can have an impact on the condition of the mother and baby if not handled properly. This study aims to determine the relationship between family support and the degree of postpartum anxiety in postpartum mothers at RSIA Kendangsari Surabaya.Subjects and Method: A cross-sectional study was conducted at Kendangsari Surabaya from July to October 2022. A total of 94 postpartum women patients at RSIA Kendangsari Surabaya were selected for this study. The dependent variable is anxiety. The independent variable is family support. The instrument used in this research is a questionnaire. Research data were analyzed using the Spearman Rho test.Results: There is a negative and moderate relationship between family support and postpartum anxiety in postpartum mothers. Postpartum mothers who received good family support reduced the degree of postpartum anxiety, and this result was statistically significant (r= -0.48; p<0.001).Conclusion: Family social support has a significant relationship with the degree of postpartum anxiety in postpartum mothers at RSIA Kendangsari Surabaya.Keywords: postpartum period; family support; postpartum anxietyCorrespondence: